Studi Kelayakan Investasi Perkebunan Kelapa Sawit PT. Agro Sinergi Nusantara (ASN) Kabupaten Aceh Selatan - Heri Tri Irawan; Iing Pamungkas (Jurnal Optimalisasi, 2020)
The oil palm plantation business is one of the businesses that are considered prospective at present. Investment to develop oil palm plantations requires large funds with a long payback period. The financial strength of investors is needed given that in the early days of plantation operations, plantation productivity was still relatively low. PT. Agro Sinergi Nusantara (ASN) is one of the national private companies engaged in the oil palm plantation sector, and plans to develop oil palm plantations covering an area of 14.000 hectares. This study aims to determine the feasibility of the business based on the financial aspects of the investment plan of PT. Agro Sinergi Nusantara (ASN) in opening an oil palm plantation in South Aceh Regency. This study uses financial feasibility analysis methods, namely net present value (NPV), internal rate of return (IRR) and payback period (PP). The final result in this study is that this investment is feasible based on net present value > 0, internal rate of return = 21,4% and payback period = 3 years.